Meningkatkan Kemampuan Berpikir Kritis Melalui Metode Eksperimen - Muhammmad Hamdani; Baskoro Adi Prayitno; Puguh Karyanto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
This study aims to explain how the experimental method applied in biology learning can improve students' critical thinking. The method used in this study is library research. This study uses secondary data in the form of scientific journals, research results and other relevant books and sources. Data analysis techniques used include three stages: organize, synthesize and indentify. The results of this study indicate that the experimental method with stages, including (1) identifying problems (2) looking for data for problem solving (3) conducting experiments (4) testing the correctness of the problem (5) making conclusions, having relevance to critical thinking indicators which include interpretation, analysis, evaluation, and decision. This paper discusses efforts to increase critical thinking in the learning process using the experimental method.